Factors Influencing Brand Loyalty among Tiktok Users - Nurhaini Binti Zulkifli (Advances in Global Economics and Business Journal, 2023)
In today’s life, social media is no longer just a platform to use for social purposes, it is more than that. People choose to spend their time on social media as they enable people to connect with one another across the globe, find career opportunities, and many more. TikTok has been super famous in this generation. The analysis shows a high probability that almost everyone knows of an app called TikTok. Statistically it can be seen from the "millennials" to "boomers" have known this application. The growth of TikTok has been rapidly increasing as it makes individuals addicted to the app itself. As TikTok took a lead in the ranking with the most active user in 2022, researches are made to define factors that influence brand loyalty among TikTok users. In this article, we can find out what factors increase users brand loyalty towards the TikTok application.